2021
DOI: 10.1177/0306624x211059316
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Positive Social Support During Reentry From Prison: Examining the Role of Volunteer Mentoring

Abstract: Social support appears to be important in improving outcomes for incarcerated individuals during the reentry process not only in terms of general wellbeing but also in gaining employment and avoiding recidivism. Mentoring programs have become increasingly popular interventions that are intended to provide such support during reentry. However, research on mentoring programs is limited and tends to focus solely on the programs’ impact on recidivism, a distal outcome. Through the use of semi-structured, in-depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In addition, we found that four commonly de ned types of social support -informational, emotional, instrumental and companionship support -were recognized by patients and coaches during the informal social network intervention [37]. These types have been identi ed and distinguished in previous work on volunteer mentoring and social support in offender populations [38,39]. In previous literature, researchers developed a model demonstrating how an intervention that leads to positive social support and commitment, resulting in positive cognitions, could in uence the impact of risk factors (i.e.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, we found that four commonly de ned types of social support -informational, emotional, instrumental and companionship support -were recognized by patients and coaches during the informal social network intervention [37]. These types have been identi ed and distinguished in previous work on volunteer mentoring and social support in offender populations [38,39]. In previous literature, researchers developed a model demonstrating how an intervention that leads to positive social support and commitment, resulting in positive cognitions, could in uence the impact of risk factors (i.e.…”
Section: Discussionmentioning
confidence: 80%
“…. These types have been identified and distinguished in previous work on volunteer mentoring and social support in offender populations(Kjellstrand, Clark, Caffery, Smith, & Eddy, 2022;Kjellstrand, Matulis, Jackson, Smith, & Eddy, 2021). In previous literature, researchers developed a model demonstrating how an intervention that leads to positive social support and commitment, resulting in positive cognitions, could influence the impact of risk factors (i.e., negative influences by peers, lack of social support) on criminal recidivism as well as substance use(Pettus-Davis et al, 2011).…”
mentioning
confidence: 99%